Advanced hydrogel material for colorectal cancer treatment - Yu Guo; Min Wang; Yuzhong Zhang; Zeyun Zhao; Jiannan Li (Drug Delivery)
Colorectal cancer is one of the most common cancers worldwide, and its incidence rates are increasing every year. Treatments for CRC include surgical resection, chemotherapy, radiotherapy, targeted therapy, and immunotherapy. Although various agents have been used in the treatment of malignant tumors, they are not as effective as expected. This is primarily owing to the lack of selectivity, poor solubility, and severe side effects of most agents. It is necessary to develop more efficient drug delivery systems for the precise targeting of the tumor site and effective therapeutic effects to meet clinical needs. A hydrogel is a three-dimensional network material composed of crosslinked side chains of hydrophilic or hydrophobic groups and a polymer backbone. Hydrogels possess useful properties including high water content, adjustable physical characteristics, elasticity, flexibility, reversible swelling, and multifunctionality. These properties render them ideal biomaterials with a broad range of applications in biomedicine and bioengineering. In this review, we introduce the pathophysiology and current therapeutic advances in CRC and summarize the applications of hydrogels composed of different materials as well as smart response hydrogels as drug carriers in CRC treatment. We also analyze the unique advantages and challenges of using hydrogels as targeted drug delivery carriers in tumor therapy.